2017
DOI: 10.1002/glia.23246
|View full text |Cite
|
Sign up to set email alerts
|

Fast Ca2+ responses in astrocyte end‐feet and neurovascular coupling in mice

Abstract: Cerebral blood flow (CBF) is regulated by the activity of neurons and astrocytes. Understanding how these cells control activity-dependent increases in CBF is crucial to interpreting functional neuroimaging signals. The relative importance of neurons and astrocytes is debated, as are the functional implications of fast Ca changes in astrocytes versus neurons. Here, we used two-photon microscopy to assess Ca changes in neuropil, astrocyte processes, and astrocyte end-feet in response to whisker pad stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 53 publications
2
75
0
Order By: Relevance
“…The direct comparison of astrocyte-neuron temporal dynamics was facilitated by the use of two different GECIs to properly segregate sub-cellular compartments in each cell type. This presents an advantage over previous studies using a single calcium indicator, which required data fitting and interpolation to detect fast astrocyte signals (Lind et al, 2013(Lind et al, , 2018. We also grouped neuronal ROIs into high, mid, and low responders (Margolis et al, 2012) based on their amplitudes and found that high responders were the most correlated and closely associated with active Lck-GCaMP6f ROIs (Figures S3F and S3G).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The direct comparison of astrocyte-neuron temporal dynamics was facilitated by the use of two different GECIs to properly segregate sub-cellular compartments in each cell type. This presents an advantage over previous studies using a single calcium indicator, which required data fitting and interpolation to detect fast astrocyte signals (Lind et al, 2013(Lind et al, , 2018. We also grouped neuronal ROIs into high, mid, and low responders (Margolis et al, 2012) based on their amplitudes and found that high responders were the most correlated and closely associated with active Lck-GCaMP6f ROIs (Figures S3F and S3G).…”
Section: Resultsmentioning
confidence: 88%
“…Astrocyte calcium signaling plays a pivotal role in the modulation of synapses (Araque et al, 2014) and local blood flow (Attwell et al, 2010); however, the temporal dynamics of these signals is currently debated (Ding et al, 2013;Gee et al, 2014;Lind et al, 2013Lind et al, , 2018Nizar et al, 2013;Otsu et al, 2015;Wang et al, 2006;Winship et al, 2007), calling into question the function of astrocytes in these brain processes. Many of these studies have focused on cytosolic calcium signals, primarily in astrocyte somata (Ding et al, 2013;Lind et al, 2013;Nizar et al, 2013;Wang et al, 2006;Winship et al, 2007), but recent work with genetically encoded calcium indicators (GECIs) has identified localized calcium signals within fine astrocyte processes (Agarwal et al, 2017;Bindocci et al, 2017;Lind et al, 2018;Otsu et al, 2015;Srinivasan et al, 2015;Stobart et al, 2018). These microdomains (MDs) can be driven by activation of the circuit and nearby neurons (Bindocci et al, 2017;Stobart et al, 2018) and they may be more relevant for information processing than large-scale calcium events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocyte function is compartmentalized, and little is known about the effect disease conditions have on the homeostasis and function of distinct astrocyte compartments (Agarwal et al, ; Dunn et al, ; Lind et al, ; Oheim, Schmidt, & Hirrlinger, ; Rungta et al, ; Shigetomi et al, ). Using saline and Ang II‐infused GLAST‐CreERT2; R26‐lsl‐GCaMP3 mice, where compartmentalized Ca 2+ activity can be readily assessed, we show increased spontaneous astrocyte Ca 2+ events in MD of hypertensive mice.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons and astrocytes generally respond to somatosensory stimulation with intensely increased Ca 2+ in neuronal somas, neuropil, astrocytic somas, processes, and end-feet (Khennouf et al, 2016; Jessen et al, 2017; Lind et al, 2018; Stobart et al, 2018). Since stroke reduces spontaneous neuronal Ca 2+ activity in adult but not aged mice, (Fordsmann et al, 2018) we next assessed how neurons in the electrically silent penumbra reacted to somatosensory stimulation during the early post-stroke period.…”
Section: Resultsmentioning
confidence: 99%